Antimicrobial drug residues in meat and their public health significance-a review - Paturkar, A M; Waskar, V S; Mokal, K V; Zende, R Z (The Indian Journal of Animal Sciences, 2005)
A rational use of veterinary drugs is one of the essential factors in the production of healthy food of animal origin, but their residues may persist in such foods. These residues are present in very small amounts and most of them do not create public health problem as long as their toxicological significance is evaluated scientifically.Antimicrobial residues in animal tissues above the legal tolerance clearly have an impact on human health. Tolerances represent the maximum level or concentration of antimicrobial residues permitted in animal tissues at the time of slaughter. The tolerances are intended to ensure that residual drugs will have no harmfull effects if ingested. This paper describes a historical review of antimicrobial use in food animals, the causes of the residues in meat, the types of the residue found, safety evaluation of the antimicrobial drug residues and their detection and quantitation methods.